Fabrication And Characterization Of Carbonate Apatite Scaffolds Coated With Alginate And Gelatin - Darus, Fadilah Mohd (2019)
Carbonate apatite (CO3Ap) has been received much attention in bone grafting due to similar chemical composition to human bone. However, CO3Ap artificial bone substitute still has not been commercialized due to the low thermal stability of carbonate at high temperature. Besides that, common limitation of porous materials, which is lack of strength should be taken into consideration. The aim of the present study is to fabricate CO3Ap scaffold using dissolution-precipitation reaction during hydrothermal treatment and to improve the compressive strength of scaffold by using natural polymer coating. Effect of two different solutions, which is NaHCO3 and Na2CO3 on β-TCP scaffold prepared via dissolution-precipitation reaction was investigated. It is found that CO3Ap scaffold with 8.95 wt.% carbonate content were successfully fabricated by NaHCO3 solution. The average pore size of the scaffold is approximately 180 μm with 72% porosity. The average compressive strength obtained of CO3Ap scaffold was 0.7 MPa. Coating of CO3Ap scaffold with alginate and gelatin was performed. Compressive strength was increased up to 1.31 MPa and 1.08 MPa, which represent 34% and 46% increment, respectively. In order to make chemical link between CO3Ap scaffold and coating, silane coupling agent A174 was used. Compressive strength of the 5SA-CO3Ap and 5BG-CO3Ap scaffold after treated with silane improved by 40% and 35%, respectively. In conclusion, treated 5SA-CO3Ap shows the highest strength with 2.17 MPa and 52% in porosity is sufficient for application of cancellous bone repair where the lowest bound for human cancellous bone is > 0.15 MPa and 50 – 90 % in porosity.